2020
DOI: 10.3390/nu12092838
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maternal BMI on Adverse Pregnancy Outcomes in Older Women

Abstract: As mothers age, the risk of adverse pregnancy outcomes may increase, but the results so far are controversial and several issues remain unknown, such as the impact of maternal weight on the effects associated with older age. In a prospective cohort of 912 Polish women with singleton pregnancies (recruited in 2015–2016), we assessed the pregnancy outcomes depending on the mother’s age (18–24, 25–29, 30–34, 35–39, and ≥40 years). Women aged ≥35 years (vs. <35 years) were assessed in terms of body mass index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…Chattrapiban et al and Heinz-Partington et al found that maternal obesity softened the effect of cigarette smoking on lower birth weight, and they explained this by the associations of maternal obesity with fetal macrosomia [21,22]. The intensification of smoking effects obtained in our study in women with obesity/overweight may be consistent with our previous articles; we presented that maternal obesity was associated not only with fetal macrosomia, but also with lower birth weight [25,34]. Importantly, in the current study, an analysis of "an ideal reference category" (never smokers with normal BMI) performed after division into BMI categories showed changes in the odds ratios of birth weight <10th percentile, FGR, and LBW in obese/overweight or underweight women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Chattrapiban et al and Heinz-Partington et al found that maternal obesity softened the effect of cigarette smoking on lower birth weight, and they explained this by the associations of maternal obesity with fetal macrosomia [21,22]. The intensification of smoking effects obtained in our study in women with obesity/overweight may be consistent with our previous articles; we presented that maternal obesity was associated not only with fetal macrosomia, but also with lower birth weight [25,34]. Importantly, in the current study, an analysis of "an ideal reference category" (never smokers with normal BMI) performed after division into BMI categories showed changes in the odds ratios of birth weight <10th percentile, FGR, and LBW in obese/overweight or underweight women.…”
Section: Discussionsupporting
confidence: 92%
“…Mitigation of the effects of smoking in obese mothers was found earlier and was explained by the relation of obesity with excessive fetal growth (and macrosomia) [21,22]. However, according to other research, obesity increases the risk of fetus growth reduction (not only macrosomia) and the risk of other pregnancy complications associated with placenta flow impairment [24,25]. This could suggest that obesity can also intensify the relations of smoking to fetus growth reduction.…”
Section: Introductionmentioning
confidence: 93%
“…At the same time, randomized studies provided good effects in the area of dietetic counselling in women with GDM [ 3 ]. In our country, nutrition standards for pregnant women are similar to the recommendations of the World Health Organization (WHO) and the European Food Safety Authority (EFSA) or the Institute of Medicine (IOM) [ 54 ], as described in our earlier study [ 25 ]. The quality of diet is also important (also shown by our earlier studies) [ 46 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current analysis, maternal characteristics were potential predictors identified in the literature as potential risk factors of macrosomia/LGA [ 1 , 2 , 3 , 8 , 10 , 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that obese women have increased risk of labour induction, labour dystocia (prolonged labour duration), instrumental vaginal delivery and caesarean delivery 8,14,17,[22][23][24][25] . The mechanism of a possible synergetic effect of obesity and age has not been evaluated in studies on labour duration with spontaneous onset 26,27 . Advanced maternal age is a risk factor for pregnancy-related complications, and the age-related decline of uterine performance is an important contributor to the increased risk of labour dystocia and caesarean delivery 13,[28][29][30] .…”
Section: Introductionmentioning
confidence: 99%